BS26 The partnerships in congenital heart disease in africa study (PROTEA): clinical characteristics and genetic findings from a South African congenital heart disease cohort. (4th June 2021) - Spracklen, Timothy; Aldersley, Thomas; Saacks, Nicole; de Koning, Bianca; Lawrenson, John; Human, Paul; Eales, James; Cupido, Blanche; Comitis, George; De Decker, Rik; Fourie, Barend; Swanson, Lenise; et al.
Abstract : Introduction: Congenital heart disease (CHD) is the most common birth defect and a significant cause of paediatric morbidity and mortality worldwide. Epidemiological data from Africa are lacking, although this information is of importance in determining the burden of CHD and guiding policy. As a multifactorial disease, the role of genetic factors in CHD is increasingly recognised. However, the genetic contribution to CHD remains relatively unexplored in Africa. The Partnerships in CHD in Africa (PROTEA) project was established to better understand the epidemiology and genetics of CHD in sub-Saharan Africa. The aim of this investigation is to describe the clinical and genetic characteristics of a cohort of CHD patients from the Western Cape, South Africa. Methods: PROTEA is a multicentre, prospective registry of CHD patients, recruited from seven hospitals in the Western Cape, South Africa. Patients with any structural CHD were eligible for inclusion, this excluded patients with isolated patent foramen ovale, peripheral pulmonary stenosis or patent ductus arteriosus in premature infants. Some of these patients were consented into the genetics study, for which a DNA biorepository was established. These patients were investigated using exome sequencing and/or chromosomal microarray (CMA) to identify disease-causing mutations or copy number variants in established CHD genes. Results: A total of 1, 473 participants were recruited into the PROTEA registry between April 2017 and March 2019 (median age 1.9 years, 51% male). Compared to international cohorts, ventricular (PR: 1.8, 95%CI: 1.63-1.97) and atrial (PR: 1.4, 95%CI: 1.20-1.57) septal defects were significantly less prevalent in PROTEA, while atrioventricular septal defects (PR: 2.2, 95%CI: 1.90-2.61), pulmonary stenosis, aortic stenosis, tetralogy of Fallot and double outlet right ventricle were significantly more prevalent. CMA analysis of 89 patients identified likely disease-causing copy number variants in five patients (5.4%), while a further 4.5% had variants of uncertain clinical significance. Using exome sequencing on 95 patients, pathogenic or likely pathogenic mutations were identified in 15 patients (15.8%); 65.3% of the sequenced cohort had variants of uncertain significance in established CHD genes. Conclusions: Preliminary analysis of the PROTEA cohort indicates that the prevalence of CHD subtypes is largely in accordance with international data, although mild lesions had a lower prevalence, and certain severe phenotypes were more prevalent. Genetic analysis of these patients demonstrates that disease-causing variants can be identified using CMA and exome sequencing, and will yield results in the expected range from international studies. Together these findings illustrate the feasibility of conducting epidemiological and genomic research amongst CHD patients in sub-Saharan Africa. Conflict of Interest: None